2020
DOI: 10.2176/nmc.oa.2020-0154
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Core Plaque Distribution Using Near-infrared Spectroscopy Is Consistent with Pathological Evaluation in Carotid Artery Plaques

Abstract: Carotid artery stenting (CAS) is performed as a treatment for carotid artery stenosis. However, lipid-rich plaques cause embolic complications and sequelae. Near-infrared spectroscopy (NIRS) can identify lipid components by applying a near-infrared absorption pattern, and the distribution of lipid components can be evaluated as the maximum lipid core burden index (maxLCBI). Intravascular ultrasound (IVUS) equipped with NIRS has been clinically applied recently, and its diagnostic usefulness and validation have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…16,17 Thyroid tissue also contains lipids with distinct NIR peaks related to C-H stretching overtones and combinations, typically between 1200 and 1300 nm. 18,19 In addition, amide linkages in thyroid tissue proteins contribute to the NIR region, allowing N-H and O-H stretches associated with protein structures to be observed in NIR. 20 Lipid, water, and protein concentrations vary in normal thyroid tissues, benign nodules, and malignant nodules.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Thyroid tissue also contains lipids with distinct NIR peaks related to C-H stretching overtones and combinations, typically between 1200 and 1300 nm. 18,19 In addition, amide linkages in thyroid tissue proteins contribute to the NIR region, allowing N-H and O-H stretches associated with protein structures to be observed in NIR. 20 Lipid, water, and protein concentrations vary in normal thyroid tissues, benign nodules, and malignant nodules.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, chemogram does not directly detect thickness of the fibrous cap covering the lipidic core (5,6). Nonetheless, it has been repeatedly demonstrated that high LCBI (i.e., lipid rich plaque) represents a vulnerable plaque and low LCBI a stable lesion (7)(8)(9)(10)(20)(21)(22)(23). High LCBI also correlates with thin cap fibroatheroma detected on optical coherence tomography imaging (24).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of lipid core with NIRS was not compared with another imaging method because there is no gold standard for plaque composition in vivo. However, the accuracy of NIRS has been recently validated on human carotid artery plaques (10). Computed tomography and magnetic resonance imaging are used to characterize carotid plaques, but their performance is largely limited by the implanted stent.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual annotations were done for five equally important classes: lipids, collagen, hemorrhages, smooth muscle cells, and background regions (including water). Two experts performed the annotation on the different regions of the sample by evaluating the staining, tissue texture and comparing the PA modulation of the annotated pixel with the literature reference spectra [33] , [34] , [35] (the criteria used to identify the spectra of the 5 classes is presented in Appendix ). Afterward, we shrunk the identified areas to exclude the signal from tissue interfaces and to account for registration mismatches ( Fig.…”
Section: Methodsmentioning
confidence: 99%